Seismic Analysis of a Two-Story Confined Masonry House: Comparative Study of Seismic-Resistant Standards E.030, NSR-10 and Nch433 - Lenin Bendezú, R. (2025)
Earthquakes are a significant threat in countries with high seismic activity such as Peru, Chile, and Colombia, where the application of earthquake-resistant regulations is essential to ensure structural safety. The objective of this research is to determine the discrepancies in the use of criteria and designs of the earthquake-resistant regulations E.030 versus Nch433 and NSR-10, as well as how these affect loads, drifts, and accelerations. This is obtained through a comparative analysis of basal shear forces, story drifts, and spectral accelerations. Therefore, a model of a two-story confined masonry house located in San Juan de Miraflores, Lima, is made using Etabs software and complying with the minimum requirements of standard E.070. NSR-10 showed the greatest strength. basal shear with a value of 422.94 Tonf on both the “X” and “Y” axes by means of analysis Linear static. On the other hand, the highest incidence of drifts with respect to their maximum permissible drifts was obtained with the E.030 standard with a value of 4.905% by linear static analysis and the highest incidence by spectral modal analysis was obtained with the same standard with a value of 5.31%. These significant differences in shear forces at the base are mainly due to the different expressions and criteria used for calculating shear, in addition to the different considerations for the use of loads in buildings. Standards E.030 and NSR-10 for calculating shear forces at the base in linear static analysis use an expression obtained from their spectra; however, the Chilean standard NCH433 does not use an expression based on its spectrum, but rather a completely different formula.